2021
DOI: 10.21037/atm-21-5539
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metagenomics and metabolomics analysis of third-trimester pregnant women with premature membrane rupture: a pilot study

Abstract: Background: Premature rupture of membranes (PROM) is a major pregnancy complication in China and usually leads to adverse pregnancy outcomes. The major aim of this study was to search for microorganisms and their related metabolites that have direct relationship with PROM.Methods: For vaginal discharge samples, metagenomics sequencing was applied to identify microorganisms that were enriched in PROM subjects, and untargeted metabolomics was applied to characterize the metabolites changes in PROM subjects compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The metabolite signature of AV is less characterised than that of BV. A study on premature rupture of membranes (PROM) patients shows that the glycolytic metabolite GalNAc (N-acetylgalactosamine) and sucrose negatively correlate with Streptococcus, Chlamydia, Prevotella, Staphylococcus, Mycobacterium, and Enterobacter genera, which supports the reduction of lactic acid (Liu et al, 2021b). In addition, Streptococcus spp.…”
Section: Microbiome Dysbiosis and Metabolite Alterationsmentioning
confidence: 98%
“…The metabolite signature of AV is less characterised than that of BV. A study on premature rupture of membranes (PROM) patients shows that the glycolytic metabolite GalNAc (N-acetylgalactosamine) and sucrose negatively correlate with Streptococcus, Chlamydia, Prevotella, Staphylococcus, Mycobacterium, and Enterobacter genera, which supports the reduction of lactic acid (Liu et al, 2021b). In addition, Streptococcus spp.…”
Section: Microbiome Dysbiosis and Metabolite Alterationsmentioning
confidence: 98%
“…The poor health care environment in India compared to other regions may have contributed to the high percentage of Enterobacter. In addition, a study found that an increase in Enterobacter in women with premature rupture of membranes was positively correlated with downregulation of glycolytic metabolites [51], which has the potential value. Moreover, a study found that Enterobacter abundance was negatively correlated with gestational age in fetal fecal and may be involved in the inflammatory response that triggers PTB [52].…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella belongs to the phylum Bacteroidetes, a common periodontal pathogen of the orange complex [ 79 ], and is associated with bacterial vaginosis [ 80 ]. Prevotella and other oral species may impair neutrophil leukocyte function and produce collagenases and fibrinolysins, which may collectively contribute to the induction of preterm birth [ 81 ]. A connection between Prevotella and preterm birth has also been reported in a study investigating the vaginal microbiome and metabolome of women with preterm membrane rupture, which found Prevotella to be among the most abundant species within the preterm membrane rupture group [ 82 ].…”
Section: Discussionmentioning
confidence: 99%